Recuperação da frequência cardíaca em crianças e adolescentes asmáticos após teste clínico de campo - Silva, Élida Pereira da (2018)
Background: Heart rate recovery (HRR) has been used to assess autonomic dysfunction, which increases the risk of cardiovascular, cardiometabolic and mortality events in several chronic diseases, in addition to being a non-invasive, low-cost and high prognostic power. Asthma is a chronic inflammatory disease that may to autonomic nervous sistem (ANS) imbalance and more sedentary behavior, however, there is a lack of evidence on the HRR in this population. Aims: To compare the HRR and functional capacity in asthmatic children and adolescents and their healthy pairs and to correlate in Asthma Group the heart rate recovery delta (ΔHRR) with age, perceived exertion, functional capacity, gravity and control of the disease. Method: Cross-sectional study. We included 77 patients diagnosed with asthma (Asthma Group - AG), with GINA 1 to 5, without hospitalization in the last four weeks and in regular treatment. Other 44 previously healthy volunteers were matched by age and gender to the AG, called the Control Group (CG). All volunteers underwent spirometry at the beginning of the protocol. Functional capacity was evaluated by the modified Shuttle test (MST) in a 10-m-long corridor. HRR was defined as heart rate (HR) at peak exercise (at the end of the MST) minus HR in the second minute after the end of the same (recovery moment), i.e., ΔRFC = HRPeak – HRrecovery. The outcome variables were: distance walked (DW) in percentage of predicted in the MST and ΔHRR. Results: The mean age of the sample was AG 11 [9-13] and CG 12 [10-14]. GA was classified as mild to moderate asthma, Step 3 [2-4] according to GINA. The pulmonary function, although different between the two groups, was within the limits of normality in both. There was delayed HRR in AG in relation to CG with significant statistical difference (ΔHRR AG = 69 ± 12 versus CG = 79 ± 15, p = 0.001). The GA had a lower percentage of predicted percentage than the predicted GC (83 ± 18% versus 95 ± 19%, p <0.001). No correlations were found between age, perceived exertion, DW in the STM, gravity and control of the disease with ΔHRR. Conclusion: we observed that asthmatic children and adolescents, even in regular control and follow-up of the disease, presented worse HRR and reduced functional capacity in relation to their healthy pairs. This information is suggestive of ANS imbalance.